Plate Size Effects in Gravelly Soil Based on In Situ Plate Load Tests and Finite Element Analysis - Wenshuai Li; Qiyu Tao; Rui Gu; Chao Li; Guoliang Dai; Weiming Gong (Applied Sciences)
The average contact stress–settlement behavior observed in plate load tests provides essential data for reliable foundation design. However, the test plate is often smaller than the actual foundation, requiring size extrapolation to interpret in situ plate load test results accurately. This study combines in situ plate load test results in gravelly soil with finite element analysis to evaluate test plates of varying sizes. The findings suggest that the coefficient of subgrade reaction for gravelly soil foundations can be effectively estimated using Terzaghi’s extrapolation method for the coefficient of subgrade reaction in clay. Although variations in test plate diameter may alter the shape of the average contact stress–settlement curve, the overall pattern of change remains consistent. The average contact stress–settlement relationship in gravelly soil can be represented by a three-phase linear model, corresponding to the elastic, yield, and failure stages. Additionally, while the elastic limit load in gravelly soil remains unaffected by plate size, the ultimate bearing capacity increases with larger plates before stabilizing.